STRATEGI INTEGRASI SISTEM TRANSPORTASI UMUM DALAM MENUNJANG PARIWISATA KOTA YOGYAKARTA - Gilang Rizki Ramadhan; Imam Buchori (Jurnal Pengembangan Kota, 2018)
The development of Yogyakarta City arises the issue of congestion that might interfere various activities, one of them is tourism activity. This aims at strategizing integration of public transport system for reducing congestion. It seeks an integration strategy of public transport system that can improve accessibility and support tourism in Yogyakarta City based on domestic tourist preference. Using descriptive statistics, service quality (servqual), and importance-performance analysis (IPA), it was revealed that respondents feel less satisfied with the quality of service of integration of public transport system, for which an improvement is needed. This can be done by strategizing integration of public transport system, from the strategy will be known the order of handling priority each variable, i.e. (1) schedule integration, (2) network integration, (3) land use integration, (4) physical integration, and (5) information integration which is done by improving its performance. Furthermore, (6) social integration, (7) environmental integration, and (8) fare and ticket integration which is done by maintaining its performance.